2018
DOI: 10.14716/ijtech.v9i1.888
|View full text |Cite
|
Sign up to set email alerts
|

A New Precipitation Hardened Austenitic Stainless Steel Investigated by Electron Microscopy

Abstract: The 56Fe16.6Cr25Ni0.9Si0.5Mn austenitic superalloy has been produced in an induction furnace; it was made from granular ferro-scrap, ferrochrome, ferrosilicon, and ferromanganese materials. Originally, this alloy had been proposed for use in high mechanical loads and high temperature conditions (such as in nuclear and fossil fuel power plant facilities). Tensile strength tests showed that the alloy has an average yield strength of about 430.56 MPa, which is higher than Incoloy A-286 (a commercially available a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…However, increasing the sintering time will ultimately decrease the islands' diameter, although it does not seem to have affected the changes in the (Cr,Fe)7C3 particle size. A similar case was also found in a study of an austenitic super alloy that was subjected to annealing and normalization, followed by various cooling rates (Dani et al, 2018). The decreasing number of eutectic structures during sintering, followed by an increase in the boundaries of inter-dendrites, will have a beneficial effect on the mechanical and physical properties for the 57Fe17Cr25NiSi super alloy.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…However, increasing the sintering time will ultimately decrease the islands' diameter, although it does not seem to have affected the changes in the (Cr,Fe)7C3 particle size. A similar case was also found in a study of an austenitic super alloy that was subjected to annealing and normalization, followed by various cooling rates (Dani et al, 2018). The decreasing number of eutectic structures during sintering, followed by an increase in the boundaries of inter-dendrites, will have a beneficial effect on the mechanical and physical properties for the 57Fe17Cr25NiSi super alloy.…”
Section: Discussionsupporting
confidence: 71%
“…To develop alloys with reliable and improved mechanical and thermal properties, various methods are used by adding different elements such as Nb, Ti, Zr, V, W, Co and Mo into the super alloy, and by the hardening of solid solutions for the matrix and hardening precipitation for both the matrix and grain boundaries. Several studies (for example, Hong et al, 2001;Geddes et al, 2010;;Fukunaga et al, 2014;Silva et al, 2017;Dani et al, 2018) have conducted heat treatment and cooling with various media to modify the microstructure of -austenite and the grain boundary to achieve alow density of (Fe,Cr)23C6 particles and Cr deflection zones. In fact, grain boundary in the austenitic super alloy may be constructed by the eutectic structures of Fe-Cr-C alloys consisting of M23C6 islands and a precipitate free zone (Choi et al, 1996); M23C6…”
Section: Introductionmentioning
confidence: 99%
“…These defects may have been induced by machining processes. These defects were also observed in previous reports for a similar sample [20] and for austenitic sample [21]. Figure 5 shows the TEM image of about 3.5 µm crosssection depth (transverse direction) from the surface of the ferritic super alloy steel sample.…”
Section: Resultssupporting
confidence: 83%
“…Next, the SIM was transformed to austenite very slowly under recrystallization, which resulted in sluggish grain growth. However, nitrogen in 253 MA ASS can promote the grain growth of austenite (Staśko et al, 2006), cerium and lanthanum, as micro-alloying can be precipitated in grain boundaries resulting in inhibited grain growth (Dani et al, 2018;Zhou et al, 2020). Previous works have also shown that V, Nb, and Ti have micro-alloyed retarded austenite grain growth (Staśko et al, 2006;Karmakar et al, 2014).…”
Section: Grain Growth Of 253 Ma and 316l Assmentioning
confidence: 99%